Untersuchungen über Gallmücken (Diptera: Cecidomyiidae). VII. Contarinia aconitifloris n. sp. aus Blütengallen von Aconitum lycoctonum L. - Stelter, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1962)
There are described the flower galls of Aconitum lycoctonum L. and a new species of gall midges reared from them. The material was found at Mühlhausen (Thuringia).Nomenclatural Actsacontifloris Stelter, 1962 (Contarinia), spec. n.